Development of a mobile phone-based intervention to improve adherence to secondary prevention of coronary heart disease in China. (16th November 2016) - Chen, Shu; Gong, Enying; Kazi, Dhruv S.; Gates, Ann B.; Karaye, Kamilu Musa; Girerd, Nicolas; Bai, Rong; AlHabib, Khalid F.; Li, Chaoyun; Sun, Kelly; Hong, Louisa; Fu, Hua; et al.
Abstract: Coronary heart disease (CHD) is a major disease burden globally and in China, but secondary prevention among CHD patients remains insufficient. Mobile health (mHealth) technology holds promise for improving secondary prevention but few previous studies included both provider-facing and patient-directed measures. We conducted a physician needs assessment survey ( n = 59), physician interviews ( n = 6), one focus group and a short cellphone message validation survey ( n = 14) in Shanghai and Hainan, China. Based on these results, we developed a multifaceted mHealth intervention that includes: (1) a provider-facing bilingual mobile app guiding prescription of evidence-based medications for secondary prevention and (2) a patient-directed short messaging system automatically sending reminders to patients regarding medication adherence and lifestyle changes (4–5 messages per week for 12 weeks). This combined intervention has the potential to improve secondary prevention of CHD and to be adapted to other countries and healthcare conditions.